Do prices in the unmediated call auction reflect insider information?: an experimental analysis - Tobias Brünner; René Levínský (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
The unmediated call auction is a useful trading mechanism to aggregate dispersed information. Its ability to incorporate information of a single informed insider, however, is less well understood. We analyse this question by presenting a simple call auction game where both auction prices and limit prices of uninformed traders reflect potential insider information. The predictions of the model are tested in the laboratory. While an insider improves the call auction outcomes in terms of increasing trading volume, uninformed traders fail to incorporate the (potential) insider information in their limit prices. We also derive an equilibrium relationship between auction returns and transaction costs similar to the relations that can be found in market microstructure models of continuous markets and which are commonly applied to estimate transaction costs. The experiment provides a good environment to assess the usefulness of this method to estimate transaction costs.
Keywords: C92; G14; D82; 330; Call auction; asymmetric information; experiment; market microstructure; Wertpapierhandel; Auktionstheorie; Insiderhandel; Börsenkurs; Mikrostrukturanalyse; Börsenspiel